Clinical Profile and Risk Factors of Patients in Stroke: A Cross-Sectional Study - Acharya, Ramesh Raj; Yogi, Nikunja; Khadka, Susmita; Kunwar, Dipak; Kunwar, Rajyashree; Shrestha, Rakshya; Karki, Adhyashree (Eastern Green Neurosurgery, 2020)
Background: In the last few decades, the incidence of stroke has doubled in low- and middle-income countries, whereas, during the same period stroke incidence has declined by 42% in high-income countries. The major type of stroke is ischemic, which occurs in about 87% of all stroke cases. According to the Global Burden of Disease (GBD) study in 2010, out of 11 million ischemic strokes occurred, among them, 63% were from a low- and middle-income country. The present study aimed to investigate the clinical presentation and risk factors of stroke patients. Materials and methods: This is a descriptive cross-sectional study. Proforma was designed for socio-demographic factors and common risk factors for stroke. A Chi-square test was conducted for a bivariate relationship between clinical presentation and stroke type. Results: Altogether 50 participants were included in the study. Among them, 58% were age 65 and over,36% belonged to the age group 45 to 65 years and 6% belonged to the age group less than 45 years. Among the risk factors, the most common risk factor was hypertension (50%). Among the clinical presentation aphasia (46%) was the most common presentation, whereas, gait abnormality (6%) and eye gaze impairment (6%) were the least common presentation. Headache and speech abnormality was significantly associated with stroke type. Conclusion: Headache and speech abnormality are significantly associated with different types of stroke.